PENGARUH KUALITAS PELAYANAN RUMAH SAKIT TERHADAP KEPUASAN DAN NIAT PERILAKU PASIEN UMUM RAWAT JALAN DI RS PKU MUHAMMADIYAH GAMPING - Muhammad Amrullah Wahid; Nuryakin Nuryakin (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2021)
Patient satisfaction is a benchmark in assessing service quality because quality of service and patient satisfaction are important in shaping patient loyalty. This study aims to investigate the quality of hospital services and their impact on patient satisfaction and behavioral intentions. This research is a Quantitative Analitical research with cross-sectional method. This research used purposive sampling method with inclusion and exclusion criteria with a sample of 120 patients. This research was conducted at PKU Muhammadiyah Gamping Hospital. Data analysis in this study uses path analysis that include regression test and sobel test which is used to determine causal relationships. With alpha 0.05, results of the test showed that service quality does not affect patient behavior intentions, service quality affects patient satisfaction, patient satisfaction affects patient behavior intentions and service quality influences patient behavior intention through patient satisfaction. It is expected that PKU Muhammadiyah Gamping Hospital can maintain the quality of services that have been given to patients, one of them is by providing training to nurses or medical personnel, so that they can improve their performance in providing the best service for patients.